2019
DOI: 10.2147/idr.s218778
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functional Synergy Of Antimicrobial Peptides And Chlorhexidine Acetate Against Gram-Negative/Gram-Positive Bacteria And A Fungus In Vitro And In Vivo</p>

Abstract: Background and purposeTo reduce the resistance and allergic reaction to chlorhexidine acetate (CHA) in the current treatment of (Bacterial vaginosis) BV and (vulvovaginal candidiasis) VVC in female vaginitis. In this study, the antimicrobial activities and mechanism of action of the synergistic effects of antimicrobial peptides (AMPs) HPRP-A1 and HPRP-A2, and CHA, against Gram-negative and Gram-positive bacteria, and one fungus Candida albicans (C. albicans) were investigated in vitro and in mouse and rat vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Reactive Oxygen Species Detection. According to Zhu's method, 26 the amounts of reactive oxygen species (ROS) in F. solani mycelium and spores were measured by a fluorometric assay with 2′,7′-dichlorofluorescein diacetate (DCFH-DA) using ROS assay kits (Solarbio Life Sciences, Beijing, China). First, the mycelium and spores of F. solani treated with AITC were collected.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Reactive Oxygen Species Detection. According to Zhu's method, 26 the amounts of reactive oxygen species (ROS) in F. solani mycelium and spores were measured by a fluorometric assay with 2′,7′-dichlorofluorescein diacetate (DCFH-DA) using ROS assay kits (Solarbio Life Sciences, Beijing, China). First, the mycelium and spores of F. solani treated with AITC were collected.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…A recent study demonstrated that low concentrations of chlorhexidine, such as the MIC, had a relatively weak effect on membrane breaking of bacteria. 63 In accordance with the protocol we selected 2⨰MIC and 4⨰MIC expecting that higher concentrations were needed for the maintenance of the effect in time (residual effect). The residual effect of chlorhexidine is well known 64 but the aim was to compare it with the nanostructured formulation.…”
Section: Development and Characterization Of Aqueous-based Chlorhexidmentioning
confidence: 99%
“…Studies of the synergy of AMPs and conventional antibiotics to reveal more effective combinations have been intensively expanding [ 155 , 156 , 157 , 158 , 159 ]. The results of the investigations have been widely surveyed [ 160 ].…”
Section: Modes Of Amp Interaction With Biological Membranementioning
confidence: 99%